MANAJEMEN KOMUNIKASI DENGAN STRATEGI KOPING (MEKANISME UNTUK MENGATASI PERUBAHAN YANG DIHADAPI) WANITA BERCADAR DALAM MENGHADAPI STIGMA SOSIAL : Studi Kasus Pada Komunitas Niqab Squad Bandung - Indah Rahmawati, - (2019)
Abstract- The arrest of the terrorist suspects in Indonesia, which was widely reported by the mass media, not only revealed the profile of a terrorist, but also presented the figures of blasting wives who used the veil. So, the veil is often associated with groups that support acts of terrorism and cause negative stigma in society. This needs to be discussed to identify problems in community life related to communication and religion, find out what motivates veiled women to wear the veil and join the Niqab Squad community, know the coping management used by veiled women in dealing with social stigma, and know what they mean in using veil. The research method used is a qualitative method with a case study approach, the type of data used is primary data through observation and in-depth interviews. The results of this study indicate that the motivation of veiled women to join the Niqab Squad community is based on several things such as friends and knowledge. Second, in dealing with social stigma, veiled women do coping management in two ways, namely problem focused coping and emotion focused coping. Third, the meaning of coping management for veiled women is an effort to build a good image in society by forming self-concept as women who are open, friendly and have good relations with the community. Keywords: Veil, Management Communication, Coping Management, Social Stigma, Veiled Women.